Masjid: Sejarah Penulisan Seni Bina Islam di Malaysia: Mosque: A History of Islamic Architectural Writing in Malaysia - Aziz, Siti Hajar; Ali @ Mat Zin, Aizan (Journal Al-Muqaddimah, 2021)
Islamic Architecture in Malaysia is one of the arts in the applied arts group. Applied art is produced to meet the demands of a function required by human beings. In contrast to other art groups, architecture not only shows the manifestation of one’s feelings and thoughts, but more importantly architecture serves to complement the needs of society. This is in line with the view of Ibn Khaldun who said that architecture is one of the characteristics of civilization that is a symbol of the glory of a nation or country. More and more buildings are developed and meet the needs of society show the progress of a civilization in this field. This article aims to sccrutinize the history of Islamic architectural writing in Malaysia in particular and compare the tendencies of the writers. Qualitative data were collected by using documentation methods and analysed by inductive, deductive and comparative methods. Findings exhibit those authors focused on the aesthetical values, designs and local genius in their works. It seems that uniformity in writing evolved unnoticed and writers inherited aspects of the discussion that had been initiated by previous scholars. In conclusion, similarities enhance uniformity in Islamic architectural writing in Malaysia